Influence of gastric emptying on gastro‐esophageal reflux: a combined pH‐impedance study. Issue 10 (12th July 2013) - Gourcerol, G.; Benanni, Y.; Boueyre, E.; Leroi, A. M.; Ducrotte, P.
Abstract Background The involvement of delayed gastric emptying (GE) in the pathophysiology of gastro‐esophageal reflux disease (GERD) remains debated and has been to date only assessed using esophageal pH‐metry that only detects acidic reflux. We therefore investigated whether delay in GE could impact on liquid, mixed, and gas reflux detected using combined esophageal pH‐impedance recording. Patients and methods Thirty consecutive patients were explored with GE and esophageal pH‐impedance measurement in the workup of typical symptoms of GERD. Gastric emptying was assessed using the 13C–octanoic acid breath test and an ambulatory esophageal pH‐impedance recording was performed off proton pump inhibitors (PPIs) for 24 h. Key Results Gastric emptying was normal in 17 patients and delayed in 13 patients. Delay in GE increased the daily number of liquid/mixed reflux events detected by combined esophageal pH‐impedance monitoring, but had no effect of esophageal acid exposure or gas reflux. This translated in increased number of postprandial reflux events, with a longer bolus clearance time and increased esophageal proximal extension. In patient with delayed GE, symptomatic reflux had a higher proximal extension and a longer bolus clearance time compared to symptomatic reflux events from patients with normal GE. Conclusions & Inferences Delay in GE increases daily and postprandial liquid/mixed reflux events. Reflux characteristics differently trigger symptoms in patients with normal and delayed GE, and may impact on the therapeutic strategy.